Surgical outcomes of cutaneous squamous cell carcinoma in the head and neck: analysis of resection margins, recurrences, and metastasis - Deffner, Felix; Schlieper, Anna Charlotta; Magradze, Givi; Becker, Christoph; Mansour, Naglaa; Knopf, Andreas; Moldenhauer, Susanne M.; Melzer, Kia; Ketterer, Manuel Christoph (Frontiers in Oncology, 2026)
IntroductionCutaneous squamous cell carcinoma (cSCC) represents the second most common skin cancer and poses a significant public health challenge. Given the rising incidence of skin cancer, it is essential to address surgical management strategies and to identify factors associated with clear resection margins, recurrence, and metastasis. This study aims to analyze the frequency of tumor-free resection margins, local recurrence, and metastasis, as well as the underlying risk factors. The central research question is: Which clinical and histopathological characteristics are significantly associated with an increased risk of incomplete resection, recurrence, and metastasis?Materials and methodsA retrospective analysis was conducted on data from 176 patients diagnosed with cSCC between 2019 and 2024. Patient data were evaluated based on clinical records, histopathological findings (including tumor thickness and depth, histological subtype, infiltration pattern, and surgical margin status), and follow-up assessments, which included routine ultrasound examinations.ResultsTumor diameter was the only independent predictor of achieving tumor-free resection margins (R0 status). Local recurrence occurred in 11.2% of patients and was significantly associated with tumor depth, whereas tumor diameter showed no correlation with recurrence-free survival. Suspicious lymph nodes on preoperative ultrasonography were detected in 3% of patients in the neck and 5% in the parotid gland. Four patients (2.2%) with suspicious findings underwent neck dissection and/or parotidectomy; synchronous metastases were confirmed in three cases (1.7%), all in cervical nodes. Further five patients (2.8%) developed metachronous lymph node metastases and were treated with surgery and adjuvant radiotherapy.DiscussionTumor depth was identified as the main determinant for achieving complete tumor resection, underscoring its prognostic relevance in cSCC. The low incidence of synchronous and metachronous lymph node metastases highlights the favorable local control achievable with adequate surgical margins and regular follow-up. The study further emphasizes the importance of early detection and structured surveillance, including regular head and neck ultrasonography, for the timely identification of metastatic disease and optimized patient management.